High temperature microstructural stability and recrystallization mechanisms in 14YWT alloys. (15th April 2018) - Aydogan, E.; El-Atwani, O.; Takajo, S.; Vogel, S.C.; Maloy, S.A.
Abstract: In-situ neutron diffraction experiments were performed on room temperature compressed 14YWT nanostructured ferritic alloys at 1100 °C and 1150 °C to understand their thermally activated static recrystallization mechanisms. Existence of a high density of Y-Ti-O rich nano-oxides (<5 nm) shift the recrystallization temperature up due to Zener pinning of the grain boundaries, making these materials attractive for high temperature applications. This study serves to quantify the texture evolution in-situ and understand the effect of particles on the recrystallization mechanisms in 14YWT alloys. We have shown, both experimentally and theoretically, that there is considerable recovery in the 20% compressed sample after 6.5 h annealing at 1100 °C while recrystallization occurs within an hour of annealing at 1100 °C and 1150 °C in the 60% compressed samples. Moreover, the 60% compressed samples show 112<110> and 112<111> texture components during annealing, in contrast to the conventional recrystallization textures in body centered cubic alloys. Furthermore, nano-oxide size, shape, density and distribution are considerably different in unrecrystallized and abnormally grown grains. Transmission electron microscopy analysis shows that oxide particles having a size between 5 and 30 nm play a critical role for recrystallization mechanisms in 14YWT nanostructured ferritic alloys. Graphical abstract: Image 1